Osada method - Magreñán, Á. Alberto; Argyros, Ioannis K (Contemporary study of iterative methods: convergence, dynamics and applications, 2021)
In this chapter the applicability of the Osada method for solving nonlinear equations is extended. Moreover, some examples are also presented illuminating the theoretical results.
Capítulo del libro "Contemporary study of iterative methods: convergence, dynamics and applications"
Keywords: osada method; local convergence; multiplicity; WOS(2)